2017
DOI: 10.1093/bib/bbx046
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide discovery of viral microRNAs based on phylogenetic analysis and structural evolution of various human papillomavirus subtypes

Abstract: In mammals, microRNAs (miRNAs) play key roles in controlling posttranscriptional regulation through binding to the mRNAs of target genes. Recently, it was discovered that viral miRNAs may be involved in human cancers and diseases. It is likely that viral miRNAs help viruses enter the latent phase of their life cycle and become undetected by the host's immune system, while increasing the host's risk for cancer development. Cervical cancer is typically related to the infection of human papillomavirus (HPV) throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Interestingly, HPV41-miRNAs and FcPV1-miRNAs are involved in the control of HPV life cycle [83]. In other recent studies, Weng et al showed that HPV-miRNAs differ in their number depending on the HPV species [15], and Virtanem et al revealed that miRNAs belonging to HPV-16 species such as miR-H1, miR-H3, miR-H5, and miR-H6 were found in tumor samples [84]. Qian et al recognized nine putative HPV-encoded miRNAs, (HPV6-mir-H1, HPV16-mir-H1, HPV16-mir-H2, HPV16-mir-H3, HPV16-mir-H5, HPV16-mir-H6, HPV38-mir-H1, HPV45-mir-H1, and HPV68-mir-H1) through tissue sequencing of human cervical lesion and cell lines.…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, HPV41-miRNAs and FcPV1-miRNAs are involved in the control of HPV life cycle [83]. In other recent studies, Weng et al showed that HPV-miRNAs differ in their number depending on the HPV species [15], and Virtanem et al revealed that miRNAs belonging to HPV-16 species such as miR-H1, miR-H3, miR-H5, and miR-H6 were found in tumor samples [84]. Qian et al recognized nine putative HPV-encoded miRNAs, (HPV6-mir-H1, HPV16-mir-H1, HPV16-mir-H2, HPV16-mir-H3, HPV16-mir-H5, HPV16-mir-H6, HPV38-mir-H1, HPV45-mir-H1, and HPV68-mir-H1) through tissue sequencing of human cervical lesion and cell lines.…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%
“…The characterization of the complete genomes of HPV subtypes by bioinformatics methods also allows the prediction of potential v-miRNAs and their target genes, providing a fundamental tool for understanding the role of HPV-encoded miRNAs in the carcinogenesis process of HPV-associated cancers [15]. Further studies are needed to discover new HPV-encoded miRNAs and their implications for both virus infection and carcinogenesis.…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the important role of long non-coding RNAs, circular RNAs, microRNAs and mRNAs in cervical cancer development and progression [2][3][4]. High-quality RNA is a pre-requisite for gene expression studies.…”
Section: Main Textmentioning
confidence: 99%
“…Several years later, the same group performed the analysis of the reported miRNAs in cervical samples by quantitative RT–PCR, and they detected low levels of expression of these miRNAs in all cases [ 198 ]. Finally, Weng et al [ 199 ] have developed a systematic method for viral miRNA identification and regulatory network construction based on genome-wide sequence analysis, and have predicted other putative miRNAs by bioinformatics approaches. The target genes of these predicted miRNAs play roles in virus infection and carcinogenesis and might be possible targets for antiviral drugs.…”
Section: Controversial Oncoviral-encoded Mirnasmentioning
confidence: 99%